Kinematics and Timing Constraints in a Transpressive Tectonic Regime: The Example of the Posada-Asinara Shear Zone (NE Sardinia, Italy) - Rodolfo Carosi (Geosciences, 2020)
Detailed geological field mapping, integrated with meso- and microstructural investigations, kinematic of the flow and finite strain analyses, combined with geochronology, are fundamental tools to obtain information on the temperature–deformation–timing path of crystalline rocks and shear zone. The Posada-Asinara shear zone (PASZ) in northern Sardinia (Italy) is a steeply dipping km-thick transpressive shear zone. In the study area, located in the Baronie region (NE Sardinia), the presence of mylonites within the PASZ, affecting high- and medium-grade metamorphic rocks, provides an opportunity to quantify finite strain and kinematic vorticity. The main structures of the study area are controlled by a D2 deformation phase, linked to the PASZ activity, in which the strain is partitioned into folds and shear zone domains. Applying two independent vorticity methods, we detected an important variation in the percentage of pure shear and simple shear along the deformation gradient, that increases from south to north. We constrained, for the first time in this sector, the timing of the transpressive deformation by U–(Th)–Pb analysis on monazite. Results indicate that the shear zone has been active at ~325–300 Ma in a transpressive setting, in agreement with the ages of the other dextral transpressive shear zones in the southern Variscan belt.